Bearing strength behaviour of bridge concrete pedestal with confined reinforcements / Mohd Raizamzamani Md Zain...[et al.] - Md Zain, Mohd Raizamzamani; Azmi Yahya, Norrul; Lee, Siong Wee; Oh, Chai Lian; Abdul Rahman, Abdul Samad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This paper deals with the bearing capacity of the unreinforced and reinforced bridge concrete pedestals/concrete blocks when concentrically loaded through square steel plate under axial compressive loading. It is well known that the presence of the lateral reinforcement gave a higher value of bearing capacity of concrete block. The main purpose of this study is to determine the ultimate bearing strength and observed the failure modes of confining reinforcement on the bearing strength of concrete blocks. A total of nine numbers of specimens with three different types of concrete pedestals was experimentally investigated. There are three specimens of concrete pedestals reinforced with ties, three specimens of concrete pedestals reinforced with spirals and three plain concrete pedestal. The use of square steel plate helps in determining the bearing capacity when concentrically loaded on top of the specimen. Experimental results indicate that the reinforced concrete blocks with spirals and ties gave larger bearing capacities than unreinforced concrete blocks. While the concrete block with higher steel percentage gave a slightly higher bearing capacity. The modes of failure between reinforced and unreinforced concrete blocks were differ between each other as the inverted pyramid and a conical shape failure occurs in the plain concrete block, while reinforced concrete block mostly gave a splitting crack on the outside of the lateral reinforcements.